Gebruikt bij manifestatiie 11-2-1974 in Krasnapolski en bij manifestatie in Groningen. Zie ook BG S10/1 en BG S10/3 en B32/450 - Koperdraat, Jan (1974)
Gebruikt bij manifestatiie 11-2-1974 in Krasnapolski en bij manifestatie in Groningen. Zie ook BG S10/1 en BG S10/3 en B32/450.